2014
DOI: 10.1038/labinvest.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-interacting protein mediates dysfunction of tubular autophagy in diabetic kidneys through inhibiting autophagic flux

Abstract: Thioredoxin-interacting protein (TXNIP) expression is ubiquitous and is induced by a variety of cellular stresses, including high intracellular glucose. TXNIP is associated with activation of oxidative stress and tubulointerstitial fibrosis in diabetic nephropathy. Autophagy is a major pathway that delivers damaged proteins and organelles to lysosomes to maintain cellular homeostasis. This study aimed to investigate the dysregulation of autophagy and the regulation of TXNIP on autophagy in renal proximal tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…Because these mouse models lack TxNIP in all cells and tissues, it is not possible to completely exclude a contribution of systemic effects (e.g., decreased inflammation) to protection from DN. However, our data in podocytes and in mesangial cells, 15 as well as in cardiomyocytes, 38,46 b cells, 13,17 and, recently, renal proximal tubular cells, 47 indicate major cell autonomous protective effects of TxNIP deficiency. The precise contribution and role of TxNIP in various cell types in the kidney to DN (i.e., endothelial, mesangial, epithelial [podocytes] and tubular cells) remain to be documented, along with tissue-specific KO mouse models.…”
Section: Discussionmentioning
confidence: 51%
“…Because these mouse models lack TxNIP in all cells and tissues, it is not possible to completely exclude a contribution of systemic effects (e.g., decreased inflammation) to protection from DN. However, our data in podocytes and in mesangial cells, 15 as well as in cardiomyocytes, 38,46 b cells, 13,17 and, recently, renal proximal tubular cells, 47 indicate major cell autonomous protective effects of TxNIP deficiency. The precise contribution and role of TxNIP in various cell types in the kidney to DN (i.e., endothelial, mesangial, epithelial [podocytes] and tubular cells) remain to be documented, along with tissue-specific KO mouse models.…”
Section: Discussionmentioning
confidence: 51%
“…Although both molecular 28 and topological 5 observations indicate that the role of TxnIP in promoting oxidative injury extends beyond its negative regulation of Trx, augmented expression of the protein has been repeatedly associated with the development of diabetes complications. 5,[29][30][31][32] In this study, we found that depletion of EZH2, with either DZNep or shRNA, rendered cultured podocytes vulnerable to the deleterious effects of high-glucose concentrations, leading to an increase in ROS levels and cell death. The augmentation of high glucose-induced oxidative damage in podocytes was, at least in part, mediated by derepression of TxnIP shown by (1) increased podocyte TxnIP mRNA and protein abundance when EZH2-depleted cells were exposed to high-glucose concentrations and (2) abrogation of ROS accumulation by either TxnIP knockdown or Trx overexpression.…”
Section: Discussionmentioning
confidence: 67%
“…High glucose levels have already been shown to inhibit autophagic turnover in several cell types, such as renal proximal tubular cells and pancreatic cells [44, 45]. However, other studies have indicated that high glucose levels can activate autophagy in cranial neural crest cells and endothelial cells [46, 47].…”
Section: Discussionmentioning
confidence: 99%